1967
DOI: 10.1021/ja00986a034
|View full text |Cite
|
Sign up to set email alerts
|

Dialkyl sulfone diimines. Synthesis, Raman spectra, chemical and physical properties

Abstract: An improved synthesis of the recently described dialkyl sulfone diimines1•2 in acetonitrile is described. Reaction of chloramine-ammonia with dialkyl sulfides in 2-propanol has been shown to yield sulfoxide and sulfone imine by-products, as well as sulfone diimines. Their formation is best accounted for by assuming that displacement of sulfur on chloramine occurs to some extent on chlorine, as well as on nitrogen. The crystalline and aqueous solution Raman spectra of dimethyl, diethyl, and methyl dodecyl sulfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
3

Year Published

1984
1984
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 0 publications
1
3
0
3
Order By: Relevance
“…It should be noted that according to the spectral data, the N‐H moieties did not participate in hydrogen bonding to a significant extent under these conditions. Stretching of the N=S=O moieties appeared as two bands at 1220–1270 cm −1 and approximately 1025 cm −1 ; these values are in agreement with the literature data for 22 and show that these fragments have similar properties in all the three compounds …”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…It should be noted that according to the spectral data, the N‐H moieties did not participate in hydrogen bonding to a significant extent under these conditions. Stretching of the N=S=O moieties appeared as two bands at 1220–1270 cm −1 and approximately 1025 cm −1 ; these values are in agreement with the literature data for 22 and show that these fragments have similar properties in all the three compounds …”
Section: Resultssupporting
confidence: 90%
“…It was found that all three compounds 20 – 22 bearing S=NH moieties were weak bases (p K a values for the corresponding conjugated acids are 3.78, 3.06, and 3.48, respectively; for 22⋅ HCl, lit . p K a =3.24±0.02).…”
Section: Resultsmentioning
confidence: 99%
“…[25] In 1989 Mock et al introduced sulfoximines [26] and sulfodiimine as analogous transition-state inhibitors for carboxypeptidase A. [27] Those functional groups are chemically stable, and with their sp 3 -hybridized [28,29] sulfur atom they successfully mimic the tetrahedral intermediate in carboxamide addition reactions. [27b] We postulate that the use of such units for backbone modifications could lead to new pseudopeptides with higher stability against enzymatic degradation and thus give rise to potential new enzyme inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Die Umsetzung des Sulfonylchlorids 6 ' ) mit 1 ad zu den N-Sulfonylschwefeldiimiden 8ad fiihrt in verdiinnter Natronlauge zu den blangelben, an der Luft stabilen 3,3-Dialkyl-l, 3 Charakterisiert wurden die Substanzen 4a -c, 9a -f und 10a -d elementaranalytisch und IRspektroskopisch anhand der gegeniiber den ringoffenen Verbindungen 3a -c, 7a -f und 8a -d fehlenden NH-Valenzschwingung im Bereich 3300 -3200 cm -' . Die Carbonylabsorption von 4 a -c und 9 a -f tritt bei 1620-1630 c m -' in Erscheincng.…”
Section: W Ried Und R Pauliunclassified